Blood microbiota diversity determines response of advanced colorectal cancer to chemotherapy combined with adoptive T cell immunotherapy. (1st January 2021) - Yang, Duo; Wang, Xiaoli; Zhou, Xinna; Zhao, Jing; Yang, Huabing; Wang, Shuo; Morse, Michael A.; Wu, Jiangping; Yuan, Yanhua; Li, Sha; Hobeika, Amy; Lyerly, Herbert Kim; et al.
ABSTRACT: Human microbiota influence the response of malignancies to treatment with immune checkpoint blockade; however, their impact on other forms of immunotherapy is poorly understood. This study explored the effect of blood microbiota on clinical efficacy, represented by progression-free survival (PFS) and overall survival (OS), of combined chemotherapy and adoptive cellular therapy (ACT) in advanced colon cancer patients. Plasma was collected from colorectal cancer patients (CRC) treated with either chemotherapy alone (oxaliplatin and capecitabine) (XELOX CT alone group, n = 19), or ACT with a mixed dendritic cell/cytokine-induced killer cell product (DC-CIK) + XELOX (ICT group, n = 20). Circulating microbiota analysis was performed by PCR amplification and next-generation sequencing of variable regions V3 V4 of bacterial 16S rRNA genes. The association of the blood microbial diversity with clinical response to the therapy as measured by RECIST1.1 and OS was evaluated. The baseline Chao index of blood microbial diversity predicted prolonged PFS and OS of DC/CIK immunotherapy. More diverse blood microbiota that included Bifidobacterium, Lactobacillus, and Enterococcus were identified among responders to DC/CIK compared with non-responders. The plasma bacterial DNA copy number is inversely correlated with the CD3 − /CD16 + /CD56 + NK cells in circulation and decreased following DC-CIK; however, the Chao index of plasma microbiota significantly increased after administration of the DC-CIK product and this subsequent change was correlated with the number of CD3 − /CD16 + /CD56 + and CD8 + /CD28 + cells infused. The diversity of the blood microbiome is a promising predictive marker for clinical responses to chemotherapy combined with DC-CIK. Cellular immunotherapy can affect the plasma microbiota's diversity in a manner favorable to clinical responses.